THE IMPORTANCE OF NEW TECHNOLOGIES IN THE SYSTEM OF HIGHER EDUCATION (Conferencea, 2023)
This article examines the importance of new technologies in the higher education system of our country, the significance of multimedia tools in teaching, their effective use, and the increasing interest of young people in the field of IT.